Analisis Desain Konseptual Sistem Pendingin Pasif Pasca Shutdown Reaktor PCMSR - Sihana; Fredrick Neo; Andang Widiharto (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2019)
Salah satu komponen terpenting dalam desain reaktor nuklir generasi ke-4 adalah pengembangan alat pendingin yang mampu bersikulasi secara alami (natural circulation). Dalam penelitian ini, telah dilakukan analisa numerik untuk mendapatkan ukuran alat penukar kalor yang masih memenuhi kriteria sirkulasi alami. Analisa dilakukan terhadap desain konseptual sistem pendingin pasif pasca shutdown dari reaktor PCMSR. Hasil penelitian menunjukkan bahwa ukuran yang diperoleh mampu memenuhi kriteria sirkulasi alami tanpa perlu adanya komponen tambahan (chimney). Analysis of Conceptual Design of Passive Cooling System Post Shutdown PCMSR Reactor Abstract: One of the most important components in the design of 4th generation nuclear reactors is the development of cooling devices that are able to naturally circulate (natural circulation). In this research, numerical analysis has been carried out to get the heat exchanger size that still meets the natural circulation criteria. Analysis was carried out on the conceptual design of the passive cooling system after shutdown from the PCMSR reactor. The results showed that the size obtained was able to meet the natural circulation criteria without the need for additional components (chimney). Keywords: Natural Circulation, Cooling System, Nuclear Reactor.